2016
DOI: 10.1186/s13062-016-0169-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity, specificity, and reproducibility of RNA-Seq differential expression calls

Abstract: BackgroundThe MAQC/SEQC consortium has recently compiled a key benchmark that can serve for testing the latest developments in analysis tools for microarray and RNA-seq expression profiling. Such objective benchmarks are required for basic and applied research, and can be critical for clinical and regulatory outcomes. Going beyond the first comparisons presented in the original SEQC study, we here present extended benchmarks including effect strengths typical of common experiments.ResultsWith artefacts removed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Library preparation was performed using the Illumina sequencing kit for high output 75-cycles for 25-30 M total single-end reads per sample. DESeq2 analyses 1 of differential expression were performed, and outliers beyond 30%-50% of the mean for each group of animals were eliminated (Love et al, 2014;Conesa et al, 2016;Labaj and Kreil, 2016;Wu and Wu, 2016).…”
Section: Rna Extraction and Rna Sequencingmentioning
confidence: 99%
“…Library preparation was performed using the Illumina sequencing kit for high output 75-cycles for 25-30 M total single-end reads per sample. DESeq2 analyses 1 of differential expression were performed, and outliers beyond 30%-50% of the mean for each group of animals were eliminated (Love et al, 2014;Conesa et al, 2016;Labaj and Kreil, 2016;Wu and Wu, 2016).…”
Section: Rna Extraction and Rna Sequencingmentioning
confidence: 99%
“…A multiplatform examination of RNA‐seq data by the Sequencing Quality Control (SEQC) project found that relative, but not absolute, gene expression measurements can be measured accurately and reliably across laboratories and RNA‐seq platforms and that RNA‐seq and microarray‐based models were comparable in clinical endpoint prediction . Current focus is on data analysis in general, where under controlled conditions reproducibility ranges from 60% to 93% . Normalisation is a particular aspect where the application of different methodologies can generate discordant results .…”
Section: Techniques Used For Rna Expression Studiesmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) was developed to characterize high-throughput gene expression profiles for populations of individual cells, which has enabled an unprecedented resolution of cellular heterogeneity in complex tissues. Widespread adoption of scRNA-seq techniques have produced large complex datasets, which present new computational challenges for evaluating experimental reproducibility and combining data from different batches and platforms [5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) was developed to characterize high-throughput gene expression profiles for populations of individual cells, which has enabled an unprecedented resolution of cellular heterogeneity in complex tissues. Widespread adoption of scRNA-seq techniques have produced large complex datasets, which present new computational challenges for evaluating experimental reproducibility and combining data from different batches and platforms [5,[7][8][9][10][11].There have been many attempts to combine gene expression data from different experiments to achieve a more comprehensive understanding of the underlying cellular heterogeneity. The first generation of tools were adapted from linear model analysis of microarrays [12][13][14] and were subsequently modified for RNA-seq data via generalized linear [15] or negative binomial models [16].…”
mentioning
confidence: 99%